Health status of dab (Limanda limanda) exposed to dumped munition in German coastal waters - Ulrike Kammann; Verena Töpker; Nicole Schmidt; Marcellus Rödiger; Marc-Oliver Aust; Michael Gabel; Jörn Peter Scharsack (PANGAEA, 2024)
Conventional munition dumped into the North Sea and the Baltic Sea close to the German coastline is corroding. A major concern is that biota, including fish, are negatively affected by toxic explosives leaking into marine environments. With the present study, we investigated fish living in close proximity to munition dumping sites for contamination and for signs of health impairments. The flat fish species common dab (Limanda limanda) was used as a model, since it lives in the vicinity of dumping sites and exhibits minor migratory activity. Various health indicators (body condition factors, externally visible fish diseases, parasites or liver anomalies) were investigated.